In vivo studies of ASC specks as antigen delivery vehicles - Yaşa, Seda. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
ASC is a 22 kDa adapter protein which is an essential component of the NLRP3, NLRC4 and AIM2 in ammasome complexes. ASC has critical functions in in ammatory and pyroptotic signaling pathways via activating caspase-1. In unstimulated cells, the ASC protein is soluble in the cytosol however upon stimulation it forms globular speck structures in close proximity to the nucleus. The importance of the ASC protein in the development of humoral immunity has been demonstrated upon vaccination of wild type and ASC knock-out mice with MF59-adjuvanted in uenza vaccine. Moreover, the importance of ASC specks in cell-to-cell communication by activation of other macrophages via phagocytosis of extracellular ASC specks after pyroptosis has been demonstrated. We previously reported that ASC specks can be loaded with the model antigen ovalbumin and OVA-loaded ASC specks can be puri- ed and fed to macrophages, which engulf the ASC-specks via phagocytosis and start degrading the protein constituents. Based on these informations, we have shown the long lasting stability of ASC specks inside the mice's bodies and its localisation to the important immune organ, spleen. Then, we checked the stimulation of immunity in in vivo mice studies using H5 (protein coat of H.In uenza virus) & OVA loaded ASC specks. Comparing the antigen speci c IgG titers, we demonstrated that we can use ASC specks as H5 antigen delivery vehicle against H5N1 virus. Also, our immunisation and tumor development experiments proved that ASC specks can be used as a novel adjuvant modality in vaccine technology. Anti-tumor e ect of ASC specks on tumor development provides an opportunity for us to improve ASC specks against tumor.
Keywords: Apoptosis.; Brain microdialysis.